Manajemen Asuhan Kebidanan Antenatal Care pada Ny “R” dengan Emesis Gravidarum di Puskesmas Mapilli Kabupaten Polewali Mandar - Sumiyati, Sumiyati; Akmasyahirah, Wulan; Adawiah, Rabiatul (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2026)
Introduction Emesis gravidarum is a common complaint of nausea and vomiting in the first trimester of pregnancy, experienced by approximately 50–80% of pregnant women worldwide. In Indonesia, and in West Sulawesi, the incidence of nausea and vomiting in pregnant women is estimated at around 55%. Although often considered a physiological condition, untreated emesis gravidarum can develop into hyperemesis gravidarum, which causes dehydration, electrolyte imbalance, nutritional disorders, and disrupts the mother's quality of life. The aim is to provide an overview and evaluate the results of midwifery care for first-trimester pregnant women with emesis gravidarum using a comprehensive approach, then documented in the form of Varney's 7 steps. Methods Obstetric management approach technique and documentation of 7 steps of Varney were used to document the data collection procedures which included observation, interview, inspection, palpation, percussion, and auscultation as well as the use of case reports. Results This study was conducted on two pregnant women in the first trimester with emesis gravidarum, namely Mrs.